2021
DOI: 10.3989/loquens.2021.080
|View full text |Cite
|
Sign up to set email alerts
|

Coronal stop lenition in French and Spanish: Electropalatographic evidence

Abstract: Lenition of voiced and, to a lesser extent, voiceless stops is widely attested in Western Romance languages. In Spanish, utterance-initial voiced stops as well as those following nasals alternate with approximants in intervocalic position. Acoustic and articulatory studies have revealed factors that condition phonetic weakening. In contrast, very little is known about stop weakening in French. In this paper, using electropalatography, we provide articulatory evidence for the lenition of /t d/ in both Spanish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Given the scarcity of published articulatory studies of French, and of Quebec French in particular, this allows us to show how the patterns observed for palatal nasals are consistent with other phonological processes reported in each variety. As we will see, the variable weakening of the palatal nasal to a velar nasal in Quebec French is consistent with other weakening processes that we have previously documented in either European or Quebec French syllable/word-finally including (i) differences in coronal stop lenition (lesser contact in the production of /t/ and, especially, /d/ in Quebec French; Colantoni et al, 2022); (ii) greater contact in the production of /n/ before alveolars (e.g., bonne tablette) by the European speakers and speaker-specific differences in the degree of the /n/-velar stop sequences (e.g., bonne casquette) compared to Quebec French (Steele et al, 2019); and (iii) reduction in anterior contact in coda versus onset-/l/ in Quebec but not European French (Colantoni et al, 2023).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Given the scarcity of published articulatory studies of French, and of Quebec French in particular, this allows us to show how the patterns observed for palatal nasals are consistent with other phonological processes reported in each variety. As we will see, the variable weakening of the palatal nasal to a velar nasal in Quebec French is consistent with other weakening processes that we have previously documented in either European or Quebec French syllable/word-finally including (i) differences in coronal stop lenition (lesser contact in the production of /t/ and, especially, /d/ in Quebec French; Colantoni et al, 2022); (ii) greater contact in the production of /n/ before alveolars (e.g., bonne tablette) by the European speakers and speaker-specific differences in the degree of the /n/-velar stop sequences (e.g., bonne casquette) compared to Quebec French (Steele et al, 2019); and (iii) reduction in anterior contact in coda versus onset-/l/ in Quebec but not European French (Colantoni et al, 2023).…”
supporting
confidence: 89%
“…In Quebec French, we predict a similar position-based asymmetry with a proportion of lenited variants word-finally. Our hypothesis for Quebec French is based on our previous EPG studies (see Introduction), where we found greater lenition in Quebec French including in the production of /d/ (Colantoni et al, 2022), and in the degree of contact reduction in /l/ (Colantoni et al, 2023).…”
Section: Current Epg Studymentioning
confidence: 79%
See 1 more Smart Citation
“…There is evidence that [continuant] is high-ranked in EF that emerges when we compare it with QF concerning the process of spirantization. The QF stop /d/ and /t/ lenite intervocalically, but they do not in EF (Colantoni et al, 2021). This differential behavior results from a difference in the ranking, as the feature does not seem to be active in either EF or QF.…”
Section: The European French Contrastive Hierarchymentioning
confidence: 92%
“…Thus, the target sounds for this phonological process are [+strident, +posterior], which is consistent with both [strident] and [posterior] being active in QF. Colantoni et al (2021) talk about coronal stop lenition using electropalatography data on two EF and two QF speakers. Interestingly, there was a significant difference between the two dialect groups in which the QF speakers showed significantly more lenition (i.e., less contact) for both /d/ and /t/, though the effect was greater for /d/ than for the EF speakers.…”
mentioning
confidence: 99%